Astronomer and geodesist prof. Bernardas Kodatis as a pedagogue, scientist and creator of independent Lithuania - Liekis, Algimantas (Geodesy and Cartography, 2011)
The end of the 19th and the beginning of the 20th century frequently put forward the name of astronomer and geodesist Prof. Bernardas Kodatis, famous for his contribution to Lithuanian national revival, the establishment of the independent State of Lithuania, creating national systems of education and the history of economic and cultural restructuring of the country. Prof. Kodatis was born and matured in Potsdam and Berlin, in German environment (his great grandfather was a Samogitian). Yet at a gymnasium, Bernardas made up his mind to be a Lithuanian, to toil and fight for the sake of Lithuania Minor, Greater Lithuania and national qualities. However, up to now, no exhaustive research generalizing his life and work activities, except for the monograph of the present author (Algimantas Liekis. Prof. Bernardas Kodatis: The Life of the Returned Lithuanian V. 2010. 410 p.) has been proposed. The questions discussed in his papers, their importance to the sciences of geodesy and astronomy in the process of creating Lithuanian education system as well as the extent of his activities significant for Lithuanian nation and the State are attempted to be answered in this article. Also, particularly relevant biographical facts and fundamental moral principles used as guidance for the personal life of Prof. Kodatis are considered. Article in Lithuanian. Astronomas ir geodezininkas profesorius Bernardas Kodatis – pedagogas, mokslininkas, nepriklausomos Lietuvos kūrėjas Santrauka. XIX a. pabaigos – XX a. pradžios lietuvių tautos atgimimo, nepriklausomos Lietuvos valstybės ir jos švietimo, mokslo sistemos kūrimo, krašto ūkinės ir kultūrinės pertvarkos istorijoje neretai galima rasti minint astronomą ir geodezininką prof. Bernardą Kodatį. Jo prosenelis buvo kilęs iš Žemaitijos. Pats gimęs ir brendęs vokiškoje aplinkoje – Potsdame, Berlyne, dar gimnazijoje apsisprendė esąs lietuvis, dirbo ir kovojo Lietuvos, lietuvių tautos labui. Iki šiol išsamesnis profesoriaus gyvenimą ir darbus apibendrinantis darbas tebuvo Algimanto Liekio monografija „Prof. Bernardas Kodatis: sugrįžusio Lietuvio gyvenimas” (Vilnius, Mokslotyros institutas, 2010. 410 p.). Straipsnyje mėginama atsakyti, kiek B. Kodačio darbai buvo ir šiandien yra reikšmingi geodezijos, astronomijos mokslams, kuriant lietuvišką švietimo sistemą, kiek jo veikla reikšminga lietuvių tautai ir jos valstybei, kokiomis moralinėmis nuostatomis profesorius vadovavosi gyvenime ir veikloje, kas reikšmingiausia jo biografijoje. Reikšminiai žodžiai: geodezininkas, astronomas, koordinatės, trianguliacija, niveliacija, gravimetrija, nepriklausomybė, tauta, lietuvybė, mokytojas, mokslininkas, topografija, UDK 528.33 Астроном и геодезист профессор Бернардас Кодатис – педагог, учёный, один из создателей независимой Литвы Резюме. Конец XIX – начало XX века отмечены возрождением литовского народа и его просвещением, началом создания системы обучения. В истории хозяйственной и культурной перестройки часто можно найти упоминание об астрономе и геодезисте проф. Бернардасе Кодатисе. Профессор родился и жил в Потсдаме и Берлине в немецком окружении (лишь его прадедушка был родом из Жемайтии), однако ещё будучи гимназистом Бернардас решает быть литовцем, работать и бороться на благо Малой и Большой Литвы и её народа. До настоящего времени не было исчерпывающей информации о его жизни и деятельности, за исключением монографии Альгимантаса Лекиса «Проф. Бернардас Кодатис: жизнь вернувшегося литовца» (Вильнюс, 2010. 410 с.). Какой же была его деятельность, насколько она актуальна для науки геодезии, астрономии, при создании литовской системы обучения, насколько она важна для литовского народа и государства, что было главным в его биографии, каких канонов морали он придерживался в жизни и деятельности? На эти вопросы автор и пытался ответить в настоящей статье. Ключевые слова: геодезист, астроном, координаты, триангуляция, нивеляция, гравиметрия, независимость, народ, национальная самобытность, учитель, ученый, солдат, артиллерист, топография, УДК 528.33 First published online: 15 Apr 2011